Effect of Thickness of Polythene Sheet and Duration of Solarization on Soil Temperature in Primary Nursery - Saresh, N.V.; Sankanur, Mahantappa; Verma, Archana; Madiwalar, S.L.; Yewale, Aalok (Indian Forester, 2013)
The study indicated that, solarization treatment receiving mulching with thin polythene sheet (0.03 mm) recorded significantly higher soil temperature at all stages. Soil temperature recorded in treatments with thin (0.03 mm), 0 medium (0.06 mm) and thick polythene sheet (0.12 mm) was 56.0, 54.4 and 53.7°C respectively. Soil temperature in primary nursery bed was significantly higher with longer duration of solarization than with short or medium duration 0 54.3, 54.4 and 55.3°C respectively. Thin (G ) or medium (G ) polythene sheet in combination with longer duration of 1 2 0 solarization (D ) significantly increased the soil temperature at all the intervals of study (57.3°C).